STARTUPS AND NEW BUSINESS MODELS IN THE FIELD OF TOURISM - Anvarova Muhsinakhon Otabek kizi (TADQIQOTLAR, 2025)
Annotation: This study explores the emergence and development of startups and innovative business models in the tourism sector. It examines the role of technological advancements, digital platforms, and entrepreneurial initiatives in reshaping tourism services, customer experiences, and market competitiveness. Special emphasis is placed on sustainable practices, the sharing economy, and smart solutions that create value for both businesses and tourists. The paper highlights the challenges and opportunities faced by tourism startups and provides insights into how new business models contribute to the modernization and diversification of the global tourism industry.